2019
DOI: 10.1021/acs.jctc.9b00571
|View full text |Cite
|
Sign up to set email alerts
|

Fully Quantum Embedding with Density Functional Theory for Full Configuration Interaction Quantum Monte Carlo

Abstract: In common with many high-accuracy electronic structure methods, the initiator adaptation of full configuration interaction quantum Monte Carlo (i−FCIQMC) has difficulty treating realistic systems with large numbers of electrons. This barrier has prevented the application of i−FCIQMC to questions of catalysis that, even for the simplest of models, require high-accuracy modeling of several features of the electronic structure, such as strong and dynamic correlation, and localized vs. delocalized bonding. We here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 98 publications
0
20
0
Order By: Relevance
“…We used EOM-CCSD as the excited-state wave function method throughout this paper; however, we see no limitations in applying this absolutely localization embedding strategy to other excited-state wave function methods as well, like the complete active space with second-order perturbation theory (CASPT2). , We are currently exploring such embedding strategies. We anticipate success since we have shown that our embedding method is robust with respect to the wave function method, at least in the ground state, by utilizing i -FCIQMC in absolutely localized projection-based quantum embedding …”
Section: Discussionmentioning
confidence: 99%
“…We used EOM-CCSD as the excited-state wave function method throughout this paper; however, we see no limitations in applying this absolutely localization embedding strategy to other excited-state wave function methods as well, like the complete active space with second-order perturbation theory (CASPT2). , We are currently exploring such embedding strategies. We anticipate success since we have shown that our embedding method is robust with respect to the wave function method, at least in the ground state, by utilizing i -FCIQMC in absolutely localized projection-based quantum embedding …”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts to fix the sign problem by leveraging this understanding directly, using a fixed-node or trial wave function approach. , The initiator approach in FCIQMC removes the annihilation plateau at the cost of introducing a small error in the energy (which can be removed by increasing the number of walkers in the simulation) . The motivation for and derivation of this approximation were ultimately related to the alleviation of the sign problem, allowing FCIQMC to be used to study a much broader scope of applications than it originally could in its canonical form. ,, The development of the initiator approximation in DMQMC achieved a similar outcome, allowing us to apply it in our previous work on the uniform electron gas and simple ab initio molecular systems. , Sign problem aside, there has recently been a slate of other improvements to FCIQMC (or FCIQMC-like) methods that are beyond the scope of this work to review in detail. Additionally, large-scale implementations of FCIQMC and related methods have also been recently developed; several recent papers that review current challenges and developments are provided for the interested reader. , …”
Section: Introductionmentioning
confidence: 99%
“…1,34 Subsequently, there were also a wide variety of FCIQMC or FCIQMC-like methods developments which are beyond the scope of this work to review in detail. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Large scale implementations of the FCIQMC method and related methods have also been developed and these papers review current challenges and developments for the interested reader. 51,52 Here, we conduct a systematic investigation of the sign problem in density matrix quantum Monte Carlo (DMQMC).…”
Section: Introductionmentioning
confidence: 99%